TRANSGENE IDENTITY AND NUMBER OF INTEGRATION SITES AND THEIR CORRELATION WITH RESISTANCE TO PStV IN TRANSGENIC PEANUTS CARRYING PEANUT STRIPE VIRUS (PStV) COAT PROTEIN GENE - Dwi Hapsoro, Hajrial Aswidinnoor, Rusmilah Suseno, Jumanto; Sudarsono . (Universitas Lampung, 2007)
Transgene Identity and Number of Integration Sites and Their Correlation with Resistance To PStV in Transgenic Peanuts Carrying Peanut Stripe Virus (PStV) Coat Protein Gene. This research aimed to determine (1) the identity and copy number of PStV cp gene in transgenic peanut plants carrying PStV cp gene and (2) correlation between the identity and the number of integration sites and resistance to PStV infection. One T0 transgenic peanut was selfed up to five generations. T2, T3, and T5 plants were mechanically inoculated with PStV. Samples of T5 plants derived from several different T4 plants were subjected to Southern analysis to confirm the integration of PStV cp gene and to determine its identity and copy number. The Southern analysis showed three bands of different size, i.e. 1.1 kb, 1.3 kb, and 5.8 kb. Most of the lines of T5 generation have one insertion site, suggesting that the three insertion sites were located in different loci. Based on the phenotypic data, the transgenes of 1.1 kb and 1.3 kb were functional, resulting in resistant or recovery phenotype, while that of 5.8 kb was not functional. Copy number apparently had no effects on the phenotypes.